2009
DOI: 10.1007/s10562-009-9992-0
|View full text |Cite
|
Sign up to set email alerts
|

Dealumination of Zeolite Beta Catalyst Under Controlled Conditions for Enhancing its Activity in Acylation and Esterification

Abstract: This work deals with the dealumination of zeolite beta (HBEA) under different conditions to optimize its catalytic performance. The dealumination was carried out either using oxalic or tartaric acid solution of different pH values or steaming up to 500˚C. The dealuminated zeolite samples were characterized using X-ray diffraction (XRD), N 2 -physisorption, ICP, 27 Al NMR and NH 3 -TPD. Their catalytic activities were studied for acylation reaction of 2-methoxy naphthalene or naphthalene with acetic anhydride a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…A large difference in total conversion was observed when the molar ratio was changed from 1:1 to 1:2 but only a marginal increase in conversion was observed on further change of molar ratio up to 1:5. 1,2-dichloroethane was found to be the best solvent for this reaction [18]. After 2 h at 333 K, only 12.5% conversion of 2-MON and 99.3% selectivity for 1-Ac,2-MON was observed.…”
Section: Catalytic Activitiesmentioning
confidence: 87%
See 2 more Smart Citations
“…A large difference in total conversion was observed when the molar ratio was changed from 1:1 to 1:2 but only a marginal increase in conversion was observed on further change of molar ratio up to 1:5. 1,2-dichloroethane was found to be the best solvent for this reaction [18]. After 2 h at 333 K, only 12.5% conversion of 2-MON and 99.3% selectivity for 1-Ac,2-MON was observed.…”
Section: Catalytic Activitiesmentioning
confidence: 87%
“…For comparative study, solid acid catalysts such as H-ZSM-5, H-BEA and Al-SBA-15 were prepared. Recently, it has been reported that the catalytic activity of zeolite beta can be significantly improved if it is dealuminated using oxalic acid at pH 2 [18]. Hence, in this study, H-BEA was dealuminated with oxalic acid at pH 2 (sample designated as H-BEA-pH2) and investigated in catalytic reactions.…”
Section: Catalyst Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the dealuminated samples exhibited an increased activity in the acylation of naphthalene and 2-methoxynaphthalene with acetic anhydride and in the esterification of benzyl alcohol with hexanoic acid due to the relative increase in the amount of strong acid sites and the enhanced accessibility of the reactants to the active sites, which is caused by removal of extra-framework Al species during the acid treatments [3]. However, these treatments also decreased the population of acid sites of weak and particularly of medium strength and as a consequence decreased the catalytic activity in the hydroisomerization of light paraffins for some Pt supported samples [4].…”
Section: Introductionmentioning
confidence: 99%
“…51 Contrariamente, en la acilación de tolueno con anhídrido acético en zeolita Beta la actividad catalítica disminuye al aumentar la relación Si/Al del catalizador, lo que sugiere que ni una mayor hidrofobicidad ni una mayor acidez producen una mejora en la actividad catalítica para esta reacción. 52 Las zeolitas desaluminizadas por tratamiento con vapor o lavado con ácido son más activas en la reacción de acilación, [53][54][55][56][57] lo que se atribuye al mayor número de centros accesibles por la eliminación de Al extrarred en los tratamientos [54][55][56] o bien a la generación de mesoporos durante la desaluminización, lo que facilitaría la difusión de reactivos y productos. 57 Así pues, no existe una conclusión definitiva acerca de la influencia de la relación Si/Al en la reacción de acilación de hidrocarburos aromáticos, aunque los resultados obtenidos sugieren que zeolitas más hidrófobas son más adecuadas para llevar a cabo la reacción, al favorecer la difusión y adsorción de reactivos y la desorción de productos.…”
Section: Reacción De Acilación De Friedel-crafts En Catalizadores Sólunclassified